Zoom Fatigue during the COVID-19 Pandemic: Is it Real? - Lestari, Putri Winda; Fayasari, Adhila (UI Scholars Hub, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused drastic changes to social lives moreover the activities done outside, such as work and school. The policy of large-scale social restrictions (LSRR)/Pembatasan Sosial Berskala Besar (PSBB), which makes people stay at home, also plays an important role in changing the face-to-face activity online. As a solution to the major change, people use video conferencing to keep in touch and still feel like doing